ʺArtificial Intelligence in modern education: challenges, opportunities and prospects for pedagogical developmentʺ - Poliakov, M. (Problems of Engineer-Pedagogical Education, 2024)
The article written by Poliakov M. V. discusses the importance of pedagogical readiness of teachers to use information technologies and artificial intelligence in the modern educational environment. The author emphasizes that modern society is experiencing rapid technological development, which requires educators to actively adapt and master new teaching methods. The creation of a teacher's information space, which includes electronic educational materials, online courses, and interactive platforms, is considered a key element of the modern pedagogical process. The importance of teachers' technical skills is combined with the necessity of understanding how to ensure effective learning interaction and support students' autonomy. It is noted that the challenges of modernity require teachers to teach using various technological tools, including artificial intelligence and virtual reality. Electronic learning platforms, which provide opportunities for online learning and distance interaction, are identified as key components of the modern information space. Additionally, the article focuses on electronic educational resources, interactivity, and personalization in teaching. In particular, the importance of using video, multimedia, and social networks to enhance the effectiveness of learning is highlighted. The main emphasis is placed on the readiness of future educators to use digital technologies as a key element of their professional competence. The integration of digital technologies into the educational process requires not only technical knowledge but also an understanding of how these technologies can improve learning and ensure the quality preparation of students. The article concludes that the modern teacher serves not only as an information mediator but also as a learning facilitator who uses innovative approaches to ensure a quality educational process. Such a teacher becomes a knowledge curator who promotes students' independent learning and actively uses digital technologies to personalize learning and adapt to different learning styles of students. In summary, the article offers a deep analysis of the challenges and advantages that modern technologies bring to the pedagogical process and identifies the need for systematic preparation of future educators to use digital technologies to ensure quality education in the era of digital transformation.